Antioxidant activity total phenolic and flavonoid content of aerial parts of Tamarix gallica - Chaturvedi S,; Drabu S,; Sharma M, (International Journal of Phytomedicine, 2012)
The present study was designed to investigate the antioxidant activities ofmethanolic extract of aerial parts of Tamarix Gallica and to evaluate the phenolic and flavonoid content of the plant. The antioxidant activity of methanolic extract was evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging and ferric-reducing/antioxidant power (FRAP) assays. The total phenolic content was determined according to the Folin−Ciocalteu procedure and calculated in terms of gallic acid equivalents (GAE). The flavonoid content was determined by the gravimetric method in terms of quercetin equivalents. The methanolic extract of aerial parts of Tamarix Gallica showed high antioxidant activity as compared to standard ascorbic acid used in the study. The results were found as 6.99498mg/100g for total content of phenols, 47.61905mg/100g for total flavonoid content and IC50of 0.5mg/ml for the antioxidant activity. Tamarix Gallica is a potential source of natural antioxidant for the functional foods and nutraceutical applications..